2018
DOI: 10.1097/aln.0000000000002376
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Epoetin-α with Intravenous or Oral Iron for Major Orthopedic Surgery

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Preoperative administration of epoetin-α with iron is commonly used in anemic patients undergoing major orthopedic surgery, but the optimal route of iron intake is controversial. The aim of this study was to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 48 publications
0
34
0
2
Order By: Relevance
“…It is also possible that the addition of ESAs to intravenous iron did not further reduce the incidence of RBC transfusion, as the increased efficacy of intravenous iron relative to oral iron may have negated any further therapeutic effect of ESA on optimal erythropoiesis. 17,19 Data from our analysis that refutes this argument include the finding that oral or intravenous iron alone did not dramatically increase the reticulocyte count (1% change with treatment). This suggests that inadequate time was allowed for the maximal therapeutic effect of iron or inadequate drug dosing prevented optimal erythropoiesis in patients treated with intravenous iron alone.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is also possible that the addition of ESAs to intravenous iron did not further reduce the incidence of RBC transfusion, as the increased efficacy of intravenous iron relative to oral iron may have negated any further therapeutic effect of ESA on optimal erythropoiesis. 17,19 Data from our analysis that refutes this argument include the finding that oral or intravenous iron alone did not dramatically increase the reticulocyte count (1% change with treatment). This suggests that inadequate time was allowed for the maximal therapeutic effect of iron or inadequate drug dosing prevented optimal erythropoiesis in patients treated with intravenous iron alone.…”
Section: Discussionmentioning
confidence: 88%
“…[16][17][18] These clinical studies and a recently published small randomizedcontrolled trial (RCT) also support the finding that intravenous iron may be more effective than oral iron at restoring iron homeostasis. 17,19 Previous systematic reviews and meta-analyses have directly assessed the efficacy of ESAs with respect to RBC avoidance. [20][21][22] Nevertheless, these studies were limited in that: 1) all relevant RCTs that assessed the efficacy of preoperative ESA therapy on RBC transfusion avoidance were not included [20][21][22] ; 2) they included studies that utilized preoperative autologous donation (PAD), which may have confounded the impact of ESAs on RBC utilization and Hb outcomes 20,21 ; 3) one study did not perform a formal meta-analysis 22 ; 4) data on all cardiac and non-cardiac surgical patient populations were not included; and 5) complete data on serious adverse effects associated with ESA therapy were not included [20][21][22] (available as Electronic Supplementary Material [ESM] eAppendix, eTable 2 and eTable 3).…”
Section: Résumémentioning
confidence: 99%
“…Several observational studies and a recent RCT have also reported on the beneficial effects of fewer rHuEPO doses in orthopedic patients, especially when combined with intravenous iron within a patient blood management program [25, 27, 44, 45] (see online suppl. Table 2).…”
Section: Treatment Options For Iron Deficiencymentioning
confidence: 99%
“…The study showed a significant reduction in the median number of red blood cell units transfused from 1 to 0, with a corresponding increase in hemoglobin concentration, reticulocyte count, and a reticulocyte hemoglobin content [19]. Similarly, a 2018 study by Biboulet and colleagues demonstrated the superior efficacy of IV iron in combination with erythropoietin relative to oral iron in patients undergoing major orthopedic surgery, showing a 0.7-g/dl larger increase in preoperative hemoglobin (p \ 0.001) [20].…”
Section: Introductionmentioning
confidence: 93%